Rehabilitation after ischemic stroke in the elderly - Paulina Kuklińska; Martyna Gackowska (Kazimierz Wielki University, 2020)
SUMMARY Introduction The article is an attempt to assess the effectiveness of various physiotherapeutic methods in people after ischemic stroke in the elderly, because rehabilitation has been shown to be an indispensable element of the treatment of these people. The range of methods used is a broadly understood concept, and this article will present the most effective reports from the world of physiotherapy on how to rehabilitate patients after a stroke. Aim The aim of the article is to characterize given methods as therapies, to indicate applications in rehabilitation and to assess their effectiveness. Methods and materials The most commonly used methods for patient improvement are NDT-Bobath, a Kabat proprioceptive pathway method (PNF). The basic therapy for the elderly after an ischemic stroke should be carried out with support for motor imagining. This article uses pilot and review works from 1986-2017. Results The presented methods of improving NDT Bobath, PNF and motor imagery are more effective in the treatment of people after ischemic stroke in the elderly than traditional methods of treatment. Research that was used for the purposes of this article conducted in the years 2009-2015 prove the effectiveness of these methods. Conclusions Based on the research carried out so far, the effectiveness of the given methods on the process of rehabilitation of a patient after a stroke can be confirmed. The use of both basic therapeutic and supportive methods at the same time gives beneficial results than using them alone. Key words: rehabilitation, stroke, neurorehabilitation INTRODUCTION A stroke is the under World Organization for a clinical syndrome characterized by a sudden onset of a focal, and sometimes also generalized brain dysfunction, the symptoms of which persist longer than 24 hours or until death and has no purpose. 80-85% of all ischemic strokes. Stroke third in time with full deaths in development after cardiovascular disease and cancer. Factors leading to pathological processes, while ischemic stroke is arterial or complete blockage of blood supply to the brain, the effects lead to hypoxia, the effects lead to damage to nerve cells [1,3]. The most important ischemic stroke is disability or weakness, sensory disturbance, involuntary movements, chorea movements, sensory and motor aphasia, maladjustment disorder [1,2].